Careers : Are you following the right to-do list?. (6th April 2017) - Snieder, Roel; Schneider, Jen
Abstract: For today's academics, balancing personal and professional demands can be a difficult, often futile task. Roel Snieder and Jen Schneider, authors of the recent book The Joy of Science, reveal the seven principles that scientists should adhere to if they want to be happy and successful